Estudos sobre a síntese de ftalocianinas anfifílicas com baixa agregação em solução - Menenguci, Cyntia de Freitas Neves (2013)
The present dissertation describe the studies conducted on the synthesis and photophysical properties of phthalocyanine dyes. The main propose of this work was to produce amphiphilic structures with low aggregation in solution. These properties are relevantfor photodynamic therapy (PDT) applications. The first synthetic methodology involved the preparation of two phthalonitriles which were previously prepared in our research group (3 and 6) (SCHEMES 1 and 2). Phthalonitrile 3 was synthesized from anhydride 1 by conversion to its corresponding tetraimide and subsequent transformation into the desired compound 3... (continue)